OP0205 Association between t follicular helper cell and plasmablast correlates with disease activity in patients with systemic lupus erythematosus. (15th June 2017) - Nakayamada, S; Kubo, S; Yoshikawa, M; Miyazaki, Y; Iwata, S; Miyagawa, I; Nakano, K; Saito, K; Tanaka, Y
Abstract : Background: Various immunological abnormalities contribute to the development and perpetuation of systemic lupus erythematosus (SLE). Since SLE is a molecularly heterogeneous disease, targeted therapy has not yet been fully established. It seems to be important to explore the characteristic and interaction among the immune cell phenotypes in this disease. Objectives: The aim of this study was to assess the relationship between the peripheral immune cell phenotypes with clinical manifestations and responsiveness to immunosuppressive therapy in patients with SLE. Methods: Peripheral blood mononuclear cells were obtained from 143 SLE patients and 26 healthy donors (HD). The blood samples were taken at baseline and week 24 after treatment. The subset of circulating B, T and dendritic cells was defined based on comprehensive 8-color flow cytometric analysis for human immune system termed "the Human Immunology Project" proposed by the National Institutes of Health (NIH) and the Federation of Clinical Immunology Societies (FOCIS). The correlation of immune cell phenotypes with clinical characteristics and responsiveness to immunosuppressive therapies, such as cyclophosphamide, mycophenolate mofetil, or calcineurin, in addition to high-dose glucocorticoids, were evaluated. Patients who were required more than two different immunosuppressant therapies in addition to glucocorticoids were considered treatment resistant. Results: The frequency of CD3 + CD4 + CXCR5 + ICOS + T follicular helper (Tfh) cell, but not CD3 + CD4 + CXCR3 + CCR6 - Th1 cell and CD3 + CD4 + CXCR3 - CCR6 + Th17 cell, were higher in SLE than that in HD (mean 1.1 vs 0.8, p=0.01). The frequency of CD19 + CD20 + IgD + CD27 + central memory B cell and CD19 + CD20 + IgD - CD27 - effector B cell were higher in SLE than that in HD (mean 23.6 vs 15.1 and 10.7 vs 5.2, p≤0.001 and p<0.001, respectively). The largest difference relative to the HD was observed in the proportion of CD19 + CD20 - CD27 + CD38 + plasmablast, which was higher in SLE (mean 16.2 vs 3.7, p<0001) and correlated with BILAG index (r=0.24, p<0.001). The proportion of Tfh cell significantly correlated with serum IgG level (r=0.35, p<0.001), and the proportion of CD3 + CD4 + CXCR5 + ICOS + CD69 + activated Tfh cell correlated with serum anti-Sm antibody level (r=0.26, p=0.01). Among helper T cell subsets (Th1, Th17, Treg and Tfh), the proportion of Tfh cell only showed positive correlation with that of plasmablast (r=0.24, p=0.02). Treatment resulted in marked improvement in disease activity scores, such as SLEDAI and BILAG and resulted in significant decreased proportions of plasmablast and Tfh cell (plasmablast; mean 17.6 to 10.1, p<0.01, Tfh; mean 1.1 to 0.7, p<0.01). The percentage of patients who showed treatment resistance was highest among patients with high percentage of Tfh cell (p=0.03). Conclusions: Peripheral immuno-phenotyping confirmed the importance of Tfh cell and plasmablast in patients with SLE, i.e. activation of Tfh cell correlated with autoantibody production while plasmablast did with disease activity of SLE. Our findings supported the relevance of Tfh cell-plasmablast axis as a potential therapeutic target for SLE. The peripheral immunophenotyping might be useful in evaluating the pathogenesis and in determining the therapeutic target of each patient. Disclosure of Interest: S. Nakayamada: None declared, S. Kubo Speakers bureau: Bristol-Myers, M. Yoshikawa: None declared, Y. Miyazaki: None declared, S. Iwata: None declared, I. Miyagawa: None declared, K. Nakano: None declared, K. Saito: None declared, Y. Tanaka Grant/research support from: Mitsubishi-Tanabe, Takeda, Daiichi-Sankyo, Chugai, Bristol-Myers, MSD, Astellas, Abbvie, Eisai, Speakers bureau: Abbvie, Chugai, Daiichi-Sankyo, Bristol-Myers, Mitsubishi-Tanabe, Astellas, Takeda, Pfizer, Teijin, Asahi-kasei, YL Biologics, Sanofi, Janssen, Eli Lilly, GlaxoSmithKline